Educational Transformation With a New Global Urgency (LEARNing Landscapes, 2010)
Education, never value-neutral, continues to be a most powerful force for shaping the next generation of global citizens and influencing the course of global development and inter-ethnic relations. Global interdependence requires that schooling can no longer serve local needs without a deeper understanding and careful consideration of global dimensions. The internationalization of education calls for a fundamental shift in the nature of teaching and learning, from "imparting the truth"to a liberal, but critical exploration and deconstruction of perspectives and their implications. An analysis of the anatomy of perspective contributes to the development of a cosmopolitan worldview which seeks to understand others with open-mindedness and mindfulness. At a more profound level, it shapes the educational enterprise in service of a universal common good.
Keywords: education; global; citizen; development; inter-ethnic; relations; universal common good; teaching; internationalization; open-minded; mindfulness